LARÓYÈ: EXU NA OBRA DE MARIO CRAVO NETO - MENDONÇA, Adriana Aparecida (2008)
The present work has themselves in the study of (re) significance of the heritage of religious and mythological deities in the african-Brazilian artistic production, with emphasis on the symbolic presence of the messenger Exu in the work of Mario Cravo Neto. In this research we seek to understand the artistic context African American and the various forms of Exu representation of the messenger, especially in contemporary photograph of the artist Mario Cravo Neto. We promote a dialogue between the mythology of the deities mainly the myths that narrates the stories of Exu, with the production of photographic series called Laróyè. This production about the African philosophy, where religion and art are not separate. The study focuses mainly on the connections that Mario Cravo Neto establish with the worship of deities, specifically the relationship between religiosity and imagery generated in the cosmology of gods Africans in Brazil and its constant changes in the face of artistic and religious diversity